COMMUNITY EMPOWERMENT FOR SUSTAINABLE DEVELOPMENT - Endah Heryanti; Akhwanul Akhmal; Supadi Bambang Sutrisno; Prihandono; Rini Mardikawanty (MANAGER: Journal of Management and Administration Science, 2025)
Community empowerment has emerged as a critical approach for achieving sustainable development, particularly in rural and marginalized regions. This article explores how empowering communities—through participatory governance, capacity building, integration of local wisdom, and technological support—can lead to long-term sustainability. Drawing from global and local case studies, this study synthesizes evidence from a semi-systematic review of empowerment programs that incorporate ecological, social, and economic dimensions. The results show that effective empowerment initiatives prioritize bottom-up participation, respect for indigenous knowledge systems, and multi-stakeholder collaboration, including NGOs, governments, and academic institutions. The role of appropriate technology and microfinance is also highlighted as enablers for fostering self-reliance and adaptive capacity within communities. Using a qualitative analytical method, the article examines various models, including the Triple Helix model, asset-based approaches, and community-led planning frameworks. It finds that sustainability cannot be achieved merely through external aid or top-down strategies; rather, empowerment must be embedded in local agency and context-specific strategies. Challenges such as weak decentralization, policy inconsistencies, and lack of access to resources still hinder many communities. Nevertheless, successful models from Indonesia, Peru, and Cameroon illustrate how integrated, community-driven development can align with global sustainability goals. This paper concludes that community empowerment is not just a means, but a foundational pillar of sustainable development. To achieve the Sustainable Development Goals (SDGs), policies must shift from tokenistic participation to authentic empowerment frameworks that are inclusive, adaptive, and resilient.